2016
DOI: 10.1371/journal.pone.0158880
|View full text |Cite
|
Sign up to set email alerts
|

Association of Renalase SNPs rs2296545 and rs2576178 with the Risk of Hypertension: A Meta-Analysis

Abstract: Background/AimsTwo renalase single nucleotide polymorphisms (SNPs) rs2296545 and rs2576178 have been reported to be associated with the susceptibility to hypertension (HT). Given the inconsistent results, we conducted a meta-analysis to assess the association between these two SNPs and the risk of HT.MethodsElectronic databases were systematically searched to find relevant studies. Subgroup analysis was conducted according to the different concomitant diseases and ethnicities in the study population. Pooled od… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 29 publications
(40 reference statements)
0
26
0
Order By: Relevance
“…Such an expression pattern would be in line with its postulated mode of action to degrade circulating catecholamines and links it to the regulation of sympathetic nervous system activity [8]. Although there has been some doubt in the literature on the "true" function of renalase [9], a number of studies showed its negative association with blood pressure [10,11].…”
Section: Article Wybraniec Et Al See P 1232mentioning
confidence: 81%
“…Such an expression pattern would be in line with its postulated mode of action to degrade circulating catecholamines and links it to the regulation of sympathetic nervous system activity [8]. Although there has been some doubt in the literature on the "true" function of renalase [9], a number of studies showed its negative association with blood pressure [10,11].…”
Section: Article Wybraniec Et Al See P 1232mentioning
confidence: 81%
“…Stec et al19 found that renalase gen polymorphism was associated with a higher risk of hypertension in patients with CKD-maintained dialysis. In the most recent meta-analysis, Lv et al33 reported that renalase gene rs2296545 polymorphism is significantly associated with an increased risk of hypertension, whereas rs2576178 polymorphism may not be associated with the susceptibility to hypertension. On the other hand, the result of the recent study of Kiseljakovic et al20 suggested that renalase gene polymorphism was not a factor that influenced BP in patients on HD.…”
Section: Discussionmentioning
confidence: 99%
“…Two independent authors evaluated the research quality according to the modified Newcastle-Ottawa scale (NOS) for genetic association study [24]. The NOS criterion is divided into three categories: (1) subject selection; (2) the comparability of subject; (3) exposure.…”
Section: Quality Assessmentmentioning
confidence: 99%